Choosing the right target: Relative preferences for resource similarity and complementarity in acquisition choice. (24th August 2015) - Yu, Yu; Umashankar, Nita; Rao, Vithala R.
Abstract : Research summary : Corporate acquisition is a popular strategic option for firms seeking new resources. However, little research exists on the question of why one firm is chosen over another. We develop a model relating characteristics of similarity and complementarity between acquirers' and target firms' key resources, including their products and R&D pipelines, to the likelihood of the acquirers choosing a particular firm. We construct measures of similarity and complementarity between and across products and R&D pipelines, and test their effects using a novel application of the choice model. Findings reveal that acquirers view similarity and complementarity differently, based on the resource they are comparing. When making comparisons to their own R&D pipelines, acquirers prefer similarity over complementarity whereas when making comparisons to their product portfolios, they prefer complementarity over similarity. Managerial summary : Corporate acquisition is a popular way for firms to grow and obtain innovative resources. However, we know little about why acquirers choose one firm over another. We capture the influence of similarity and complementarity between acquirers' and target firms' products (current innovative value) and R&D pipelines (future innovative value) on whether a particular target firm is acquired. Insights from the pharmaceutical industry reveal that acquirers value similarity and complementarity in target firms differently, based on whether the comparison being made is with respect to their products or their R&D pipelines. Regarding their R&D pipelines, acquirers prefer that the target firm has similar, rather than complementary, resources. However, the opposite is true concerning their own products: acquirers prefer that the target firm has complementary, versus similar, resources. Copyright © 2015 John Wiley & Sons, Ltd.